Tunable thermal conduction character of graphite-nanosheets-enhanced composite phase change materials via cooling rate control. (October 2015) - Fang, Xin; Ding, Qing; Li, Li-Yi; Moon, Kyoung-Sik; Wong, Ching-Ping; Yu, Zi-Tao
Highlights: Ball milling is suitable for controlling the size of graphene nanosheets. 258% increase in thermal conductivity was achieved by the largest GNS-30 at 5 wt.%. Thermal stability of PCMs was improved by graphite nanosheets. Larger crystalline size of PCM results in higher thermal conductivity. Inclusions increase the sensitivity of thermal conductivity of PCMs to cooling rate. Abstract: This work is concerned with the influence of cooling rates on the thermal conduction behavior of nano-enhanced PCMs for thermal energy storage. 2-dimensional graphite nanosheets of different sizes have been applied to prepare the eicosane-based composite PCMs. Comprehensive measurements on the thermal storage properties of the prepared composite PCMs were also performed considering the factors including particle size as well as loading level. Results strongly revealed the tunable thermal conduction behavior of the solid-state composite PCMs versus cooling rate. As the cooling rate was ascended from 2.03 to 30.94 °C/min, more than 25% drop of the solid-state thermal conductivity was observed for the samples containing graphite nanosheets. Besides a percolation threshold around 1 wt.%, measured thermal conductivities increased linearly with the particle concentration, achieving the highest value of 1.57 W/m K by GNS-30 at 5 wt.%. Moreover, the graphite nanosheets with a larger size were found to cause higher improvement in thermal conductivity, and also the relatively higher viscosity of PCM suspensions. DSC results indicated the decrease in latent heat capacity of samples is negligible after the incorporation of graphite nanosheets.